Rancang Bangun Aplikasi Seleksi Penerimaan Mitra Kerja Pengadaan Beras Bulog Subdivre Surabaya Utara - Raharjo, Anggi Prasetyo Wahyu; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Badan Urusan Logistik (BULOG) is a state-owned company engaged in the food logistics. According SOP Admission Selection of Bulog Partners, selection begins in November or December in the previous year and be completed by the end of the year. Selection acceptance rice procurement partners at this time began from December until February. The procurement of rice at the beginning of the year will be delayed due to the selection and classification process has not been completed, so there is no partner that receives cooperation contract procurement. As a result, the procurement rice in the early year almost non-existent. Another problem is the lack of information to potential partners selected. From those problems, it created Application selection acceptance working partners that will handle the admissions process to prospective partners and send report either. This application is built based on the web and also using the Short Message Service (SMS) as media solution delivering an information selection and classification result to the prospective partners.The results from testing application selection working partner procurement has been implemented in BULOG Subdivre North Surabaya can be concluded that the application that created can run 100 percent success and can help the verification process the requirements, selection, classification and making report, so that the problem of delay the selection process and deliver information to prospective partners can be resolved. Keywords: Acceptance, Partners, Verification, Classification